2004
DOI: 10.1128/aac.48.7.2400-2408.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Evolution of the Class A Chromosomal Beta-Lactamase Gene inKlebsiella pneumoniae

Abstract: We investigated the diversity of the chromosomal class A beta-lactamase gene in Klebsiella pneumoniae in order to study the evolution of the gene. A 789-bp portion was sequenced in a panel of 28 strains, representative of three phylogenetic groups, KpI, KpII, and KpIII, recently identified in K. pneumoniae and of different chromosomal beta-lactamase variants previously identified. Three groups of sequences were found, two of them corresponding to the families SHV (pI 7.6) and LEN (pI 7.1), respectively, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
116
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 51 publications
(42 reference statements)
10
116
0
Order By: Relevance
“…Due to the growing number of Klebsiella species that possess plasmid and chromosomally encoded bla SHV-enzymes, the traditional iso-electrofocusing technique appears not to be the method of choice for discriminating between a K. pneumoniae bla SHV, bla LEN and bla OKP-genotype any longer [9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the growing number of Klebsiella species that possess plasmid and chromosomally encoded bla SHV-enzymes, the traditional iso-electrofocusing technique appears not to be the method of choice for discriminating between a K. pneumoniae bla SHV, bla LEN and bla OKP-genotype any longer [9].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Haeggman and co-workers [9] identified a new, third group of sequences related to the bla SHV and bla LEN families, namely the chromosomally encoded bla OKP family (for other K. pneumoniae β-lactamase). To date, 14 different bla OKP-type β-lactamases have been described [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations